2018
DOI: 10.1080/1057610x.2018.1529353
|View full text |Cite
|
Sign up to set email alerts
|

Female Fighters and Militants During the Lebanese Civil War: Individual Profiles, Pathways, and Motivations

Abstract: This article offers an analysis of women's profiles, pathways, and motivations to join the Lebanese civil war (1975 to 1990), with a particular focus on female fighters militants involved with Harakat Amal, Kataeb, the Progressive Socialist Party, Lebanese Communist Party, Fatah and the Popular Front for the Liberation of Palestine. The article contributes to existing debates on women's motivations to join nonstate armed groups by examining both militias that included female fighters and those that did not. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Twenty (20) e-interviews with women fighting on the pro-Ukrainian side revealed that patriotism and a desire to protect one's country from a hostile foreign force that questions the very existence of the state was the main predominant motive. Other motives, also described in similar research projects (e.g., J. P. Eggert (2018); J.T. Darden et al (2019)) were also found while analyzing the interview data.…”
Section: Discussionsupporting
confidence: 60%
“…Twenty (20) e-interviews with women fighting on the pro-Ukrainian side revealed that patriotism and a desire to protect one's country from a hostile foreign force that questions the very existence of the state was the main predominant motive. Other motives, also described in similar research projects (e.g., J. P. Eggert (2018); J.T. Darden et al (2019)) were also found while analyzing the interview data.…”
Section: Discussionsupporting
confidence: 60%
“…Peteet (1991) suggests that the PLO trained women in military camps but did not regularly incorporate them as fighters. Eggert (2018), in contrast, estimates that women may have comprised up to 15% of fighters between 1975 and 1990. PFLP posters regularly link women’s liberation with national liberation, though Sayigh (1981) contends that these arguments are not reflected in PFLP praxis.…”
Section: Armed Mothers In Militant Visualsmentioning
confidence: 99%